Histopathological comparison between experimental Streptococcus agalactiae and Streptococcus iniae infections in Oreochromis sp. - Jamalludin, Dzulkifli (2018)
Streptococcus agalactiae and streptococcus iniae are two main pathogens contributing to streptococcosis in fish. Streptococcosis is an important disease, leading to economic losses in aquaculture industry. The aim of this study was to compare the histopathological evaluations between S. agalactiae and S. iniae infections in Oreochromissp.. Two experiments were conducted. In the first experiment, 60 healthy fish with the size of less than 4” were divided equally into three (3) groups; one control (G1) (n=20) and two treatment groups (G2, G3) (n=20) each. Each group was further divided equally into two groups, consisting of 10 inoculated fish and 10 fish were not inoculated but served as commingling fish. The former were inoculated with sterile PBS, S. agalactiae, and S. iniae, intraperitoneally at the rate of 0.03 ml/g of 1x107 cfu/ml of bacteria. In the second experiment, the same experimental design was used, with the exception of the size of fish. Fish with more than 4” were used. G4 was inoculated with sterile PBS, G5 was inoculated with S. agalactiae, and G6 was inoculated with S. iniaeat the aforementioned rate. All fish were observed every 6 hours for a period of 5 days. During the observation period, any dead fish was subjected to necropsy. After the observation period, any remaining fish were euthanized for necropsy. Samples of spleen, liver, and brain were collected and fixed in 10% neutral buffered formalin, and subjected to routine histopathology process. Gross lesions observed included cerebral oedema, ascites, integumentary haemorrhage, presence of pustules, and intestinal congestion. Tissue section of each organ was examined under microscope at 40x magnification and lesions were described and scored. In all infected groups, infiltration of inflammatory cells and haemorrhage were the most frequently observed lesion. All groups infected by S. agalactiae showed significantly (p<0.05) more severe lesions compared to the groups infected by S. iniae, regardless of the size.Significant difference (p<0.05) was also observed in comparison between the lesion score in fish of different sizes. Fish of more than 4” showed higher lesion severity score compared to fish of less than 4”. In both streptococcosis, S. agalactiaeis more pathogenic than S. iniaein Oreochromissp., and fish more than 4” is more susceptible towards both streptococcosis.